A survey in using ontologies and rules reasoning in access control system - Gicquel, Pierre-Yves (2022)
In today’s heavily cloud distributed-service period, access control systems are primary components to guarantee security and con- fidentiality of resource repositories. However, access control systems most widely used were deigned before this period of generalized service based infrastructure. This creates important difficulties in the maintenance of such systems. New approach in access control system, based on a formal and logical approach of security rules have been proposed that makes use of the semantic web technologies. In this paper we propose a survey of these semantic approaches together with a comparison of their respective strength depending on the considered use case.